Determination of chlorogenic acid as one of the major antioxidants in commercial tea and coffee samples - Grujić-Letić, Nevena; Rakić, Branislava; Šefer, Emilia; Rakić, Dušica; Nedeljković, Ivan; Kladar, Nebojša; Božin, Biljana (Vojnosanitetski pregled, 2015)
Background/Aim. Tea and coffee are one of the most widely consumed beverages in the world due to their beneficial health effects which are largely associated with their phenolic compounds composition, including chlorogenic acid. The main goal was to determine chlorogenic acid, as one of the major antioxidants, in various commercial tea and coffee samples present at the Serbian market. Experimental. A High-performance liquid chromatography (HPLC) method for determination of chlorogenic acid in plant extracts was applied to determine the content of 5-caffeoylquinic acid (5-CQA) in commercial tea and coffee samples. Mobile phase was aqueous 1.5% acetic acid - methanol (80:20) with a flow rate of 0.8 mL/min. Run time was 15 min and column temperature 25° C. The detection was performed at 240 nm. Results and discussion. HPLC method was modified and re-validated. The chlorogenic acid content varied depending on the type of tea (white, green, black tea and mate) and the processing technology which is unique for each producer. Green tea had the highest 5-CQA content (16 mg/100 mL) among the analyzed tea samples. The content of 5-CQA in coffee samples ranged 0-46.98 mg/100 mL and obtained results showed that chlorogenic acid content varied depending on the type of coffee, coffee processing technology and the formulation. Conclusion. Modified and re-validated HPLC method showed good accuracy, repeatability, selectivity and robustness. The highest amount of 5-CQA was obtained in green tea in comparison to white, black and mate tea because the increased oxidation level decreases the amount of chlorogenic acid. Obtained results for commercial coffee samples indicated that the formulation is the most important factor determining the amount of chlorogenic acid intake. It can be concluded that plant material selection and processing conditions have great influence on the amount of chlorogenic acid in the final tea and coffee products.